Many Excellent People : Power and Privilege in North Carolina, 1850-1900. - Escott, Paul D. (University of North Carolina Press, 1988)
Many Excellent People# examines the nature of North Carolina's social system, particularly race and class relations, power, and inequality, during the last half of the nineteenth century. Paul Escott portrays North Carolina's major social groups, focusing on the elite, the ordinary white farmers or workers, and the blacks, and analyzes their attitudes, social structure, and power relationships. Quoting frequently from a remarkable array of letters, journals, diaries, and other primary sources, he shows vividly the impact of the Civil War, Emancipation, Reconstruction, Populism, and the rise of.